READING ALOUD STRATEGY FOR ENHANCING STUDENTS’ SPEAKING ABILITY - Rika Sri Erdila; Mutiara Harahap; Nurul Hasanah; Miranda Gultom; Nurjakiah Harahap (Program Studi Pendidikan Bahasa Inggris, 2026)
The aims of this research are to know 1) the extent is the application of the reading aloud strategy in teaching speaking ability, 2) the extent is the students' speaking ability before and after using the reading aloud strategy, 3) is there any significant effect of the reading aloud strategy on students' speaking ability in class XI SMA Negeri 8 Padangsidimpuan. This research used experimental method with pre-experimental one group pretest-posttest design. The population of this study was all XI grade which amounted to 98 students. The sample of this study was class XI 1 which amounted to 32 students taken by cluster sampling. Data were collected through observation and tests as instruments. Data collection technique for observation sheet used Liket scale and speaking test used speaking rubric. The results showed that the application of reading aloud strategy reached 89% (very good category). The average value of students' speaking ability before and after using the reading aloud strategy is 43.19 (poor category) and 78.53 (good category). The results of hypothesis testing using the Normality Test with SPPS 23, showed that the paired sample t-test pretest and post-test tables were smaller than 0.05 (0.000 <0.05). it means that the hypothesis (H₂) is accepted. there is a significant effect of the reading aloud strategy on students' speaking ability in the eleventh grade of SMA Negeri 8 Padangsidimpuan.